Sex differences in pituitary corticotroph excitability - Duncan, Peter J.; Romanò, Nicola; Nair, Sooraj V.; Murray, Joanne F.; Le Tissier, Paul; Shipston, Michael J. (Frontiers in Physiology, 2023)
Stress-related illness represents a major burden on health and society. Sex differences in stress-related disorders are well documented, with women having twice the lifetime rate of depression and most anxiety disorders. Anterior pituitary corticotrophs are central components of the hypothalamic pituitary adrenal (HPA) axis, receiving input from hypothalamic neuropeptides CRH and AVP, while regulating glucocorticoid output from the adrenal cortex. The dynamic control of electrical excitability by CRH/AVP and glucocorticoids is critical for corticotroph function, however whether corticotrophs contribute to sexually differential responses of the HPA axis, which might underlie differences in stress-related disorders is very poorly understood. Using perforated patch clamp electrophysiology in corticotrophs from mice expressing GFP under the control of the Pomc promoter, we characterised basal and secretagogue-evoked excitability. Both male and female corticotrophs show predominantly single-spike action potentials under basal conditions, however males display predominantly spikes with small amplitude (<20mV) afterhyperpolarisations (B-type) whereas females displayed a mixture of B-type spikes and spikes with a large (>25mV) afterhyperpolarisation (A-type). In response to CRH, or CRH/AVP, male cells almost exclusively transition to a predominantly pseudo-plateau bursting whereas only female B-type cells display bursting in response to CRH±AVP. Treatment of male or female corticotrophs with 1nM Oestradiol (E2) for 24-72h has no effect on the proportion of cells with A- or B-type spikes in either sex. However, E2 results in a cessation of CRH-induced bursting in both male and female corticotrophs, which can be partially reversed by adding a BK current with dynamic clamp. RNA-seq analysis of purified corticotrophs reveals extensive differential gene expression at the transcriptional level including more than 71 mRNAs encoding ion channel subunits. Interestingly, there is a 2-fold lower level (p<0.01) of BK channel pore-forming subunit (Kcnma1) expression in females compared to males, which may partially explain the decrease in CRH-induced bursting. This study has identified sex differences at the level of anterior pituitary corticotroph ion channel landscape and control of both spontaneous and CRH-evoked excitability. Determining the mechanisms of sex differences of corticotroph and HPA activity at the cellular level could be an important step for better understanding, diagnosing and treating stress-related disorders.